THE ROLE OF SUSTAINABLE FINANCE IN PROMOTING ECONOMIC AND SOCIAL DEVELOPMENT ON ISLAMIC BANKS - Alsari, Hussein Ali Saad (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Islamic financial organizations, which work in agreement with Sharia law, assimilate financial innovation with social accountability in instruction to challenge global issues relating to sustainability and inclusivity. This academic article explores the means in which Islamic banks ease economic and social progression done performs of sustainable finance. Finished a proportional analysis of the financial crops providing by Islamic banks and their conservative complements, the study clarifies the important role played by Islamic financial institutions in development long-term economic growth, justifying differences, and indorsing social wellbeing. Also, the study inspects the distinctive physiognomies of Islamic banking, counting the exclusion of interest and the ordering of moral investment, and evaluates their possible to challenge expansion trials within the MENA region. The study achieves with references aimed at supplementing the bulk of Islamic banks to further donate to economic and social expansion, in al Islamic financial determined with global sustainability objectives.